Understanding the universe what's new in asronomy, 2003 - Filippenko, Alexei V.; Teaching Company (Chantilly, VA Teaching Company, 2003)
Professor Alex Filippenko of the University of California at Berkeley delivers 16 lectures on the universe.
Pt.1. From dawn to dusk -- Exploring the night sky -- Recent discoveries in our solar system -- Other worlds galore! -- The formation and evolution of stars -- Supernovae : catastrophic stellar explosions -- Gamma ray bursts and the birth of black holes -- Observational evidence for black holes -- pt.2. Einstein's relativity -- Cosmology and cosmic expansion -- The birth and evolution of galaxies -- The accelerating expansion of the universe -- The stuff of the cosmos -- Dark energy : may the force be with you -- Theories of everything, and hidden dimensions -- Our universe, one of many?
16 lectures (45 min. each) in 2 parts.
Course guides include an outline of each lecture and bibliographical references.
"Course no. 190".--Disc.
Teaching Company: PD190-01--PD190-02.
Alex Filippenko, lecturer.
DVD.
Keywords: Cosmology; Lecture